Navigating Change: A Comprehensive Analysis of Current Financial Trends in the United States - Ali, Md. Mokshud; Tabassum, Tanbina (International Journal of Management and Digital Business, 2024)
This research study offers a comprehensive overview of current advancements in financial practices in the United States. This research will examine recent shifts in American financial habits and offer stakeholders guidance on how to effectively manage the evolving financial landscape. A thorough assessment of prior literature reviews and empirical studies on digital finance in the US is part of the research methodology.The literature review focuses on how developments in financial technology (FinTech), regulatory changes, a growing emphasis on sustainability, and shifting consumer behavior have significantly altered the financial sector.. The influence of regulatory barriers, ESG integration, evolving consumer behavior, and the complex interactions affecting US financial practices are the main topics of discussion. The results underscore the significance of digital transformation, regulatory impediments and campaigns, consumer inclinations, the advantages and challenges of decentralized financing (DeFi), and cybersecurity and privacy issues. Recommendations are provided based on the results to enhance regulatory flexibility, raise financial literacy and awareness, fund cybersecurity infrastructure, encourage cooperation and information exchange, welcome responsible innovation, and track and react to market dynamics. By putting these recommendations into practice, stakeholders can better navigate the complexity of digital banking in the US and foster innovation, inclusion, and trust in the digital financial ecosystem while averting the dangers and difficulties that come with it.